The Relationship between Information Literacy and Knowledge Management among Students and Faculty Members of Shiraz University - Hemmati, Mozghan (International Review of Management and Marketing, 2017)
Universities as the main knowledge creation centers in society need to strengthen their information literacy and knowledge management skills in order to achieve their objectives. In this regard, the aim of this study is to investigate the relationship between information literacy and knowledge management in academic environments. The statistical population of the research includes students and faculty members of Shiraz University. The stratified random sampling method is used and the sample size is determined 136 students and 54 faculty members by using Morgan table. To collect the necessary data, two questionnaires of information literacy and knowledge management have been used. To assess the level of information literacy and knowledge management, descriptive statistics is used and to investigate the relationship between information literacy and components of knowledge management, nonparametric Kolmogorov-Smirnov test and Spearman correlation coefficient are used. The findings show that the level of information literacy is estimated 3/30 for students and 3/60 for faculty members which are higher than average. The evaluation of the components of knowledge management showed that knowledge management is estimated an intermediate level (3/02) for students, and higher than the average (3.19) for faculty members. There is a significant relationship between students' information literacy and components of knowledge creation and knowledge storing. There are significant relationships between Information literacy of faculty members and the four components of knowledge management (creation, storage, sharing, and application). Finally, recommendations are provided according to the results to promote information literacy. Keywords: information literacy, knowledge management, students, members of faculty, Shiraz University JEL Classification: D8